Influência da rigidez da parte anterior da entressola do tênis no deslocamento angular do pé e na potência de joelho durante a marcha - Renan Alves Resende (2011)
Introduction: The compression stiffness of the midsole at the forefoot may influence the kinematics and the kinetics of the lower extremity. It is possible that a midsole with low stiffness may increase the angular displacement of the foot segments and increase the power of the lower extremity. Purpose: Evaluating the influence of the stiffness of the forefoot midsole on the motion of the segments of the foot, knee andhip and on the power of the ankle, knee and hip during the stance phase of gait. Method: Three-dimensional kinematics and kinetics data of the lower extremity of 37 healthy subjects, wearing two different levels of forefoot midsole shoe stiffness (lowstiffness and high-stiffness conditions), were obtained during the stance phase of gaitusing the Qualisys ProReflex synchronized with a force platform. The dependent variables were: forefoot and rearfoot motion in the frontal and transverse planes; knee and hip motion in the transverse plane; sagittal power at the ankle, knee and hip joints. Data were analyzed by first extracting the total range of motion from the forefoot and rearfoot waveforms and by applying principal component analysis toextract the shape and magnitude differences from the waveforms between conditions. Results: Low-stiffness condition had a higher range of motion in the transverse plane of the forefoot and rearfoot than the high-stiffness condition (=0.05). The principal component analysis detected magnitude and waveform characteristics that were significantly different between conditions. Conclusions: The findings suggest the influence of the compression stiffness of the forefoot midsole on the kinematics of the segments of the foot and on the power generation atthe knee joint during the stance of gait. The low-stiffness condition was associated with a delay in the generation of energy during late stance which may negatively influence the performance during gait.